Evaluation of accuracy and reliability of OneCeph digital cephalometric analysis in comparison with manual cephalometric analysis-a cross-sectional study - Akshay Mohan; Arvind Sivakumar; Prasad Nalabothu (Nature Publishing Group, 2021)
Abstract Introduction Lateral cephalometric analysis continues to be one of the gold standard diagnostic aids in orthodontics, with various software available to enhance this. Aim This study was done to evaluate the accuracy and reliability of linear and angular measurements obtained from OneCeph digital cephalometric tracing and manual tracings in lateral cephalometry. Methodology This is a cross-sectional study done on twenty pre-treatment lateral cephalometric radiographs of subjects who reported to the postgraduate orthodontic clinic for orthodontic treatment over one month. Cephalometric tracings were done using OneCeph digital software and manual tracing method to evaluate nine parameters of Steiner's cephalometric analysis. An Independent T-sample test was done between the mean values of manual and OneCeph tracing. Intra operator reliability was evaluated by paired T-test after a week. Results No significant statistical difference was observed as the p-value was greater than 0.05 for all the parameters in the two groups. Conclusion The reliability and accuracy of OneCeph software application was found to be at par with manual cephalometric tracing